PRIORITY ISSUES OF CHILD EDUCATION IN THE FAMILY - Sidikova Zarema Rakhmonberdievna (American Journals, 2024)
As we all know, in our country, a unique national upbringing has begun to take shape in families. Family moral education is one of the integral components of this process. Young parents need to conduct targeted pedagogical-psychological conversations with their children, it is necessary and necessary to pay attention to every word of the child. "You don't know anyway" and we begin to influence the child's psyche. We need to know that proper education and upbringing in the family should be attentive to every word of the children of the growing age and listen patiently in the era of global change. We parents make a great contribution to the fact that the child grows up to be responsible, intelligent, polite and courageous.
Keywords: Family, child, upbringing, education, society, country, skill, skill, neighborhood, environment.